Perlindungan Anak di Era Kapitalisme Platform: Revitalisasi Pembatasan Akses Media dan Penguatan Kedaulatan Digital - Sutag Harsie; Muhammad Hanafi; Kuswandi Dwi Eri Edisam; Iranda Nadya Febianty; Rahmatullah Ayu Hasmiati (Universitas Muhammadiyah Kotabumi, 2026)
The development of digital technology and platform-based media has transformed patterns of social interaction, communication, and information access, particularly among children as active users of digital spaces. The dominance of global digital platforms such as YouTube, TikTok, Instagram, and WhatsApp has generated various new risks, including exposure to harmful content, cyber exploitation, digital surveillance practices, and the commodification of children’s personal data. This study aims to analyze the revitalization of media access restrictions for children from the perspectives of child protection and digital sovereignty in the era of platform capitalism. The research employs a doctrinal (normative legal) method using statutory, conceptual, and comparative approaches. The findings indicate that the crisis of child protection in digital spaces is not merely caused by regulatory gaps, but also by structural inequalities between states and transnational digital corporations that control data, algorithms, and digital platform governance. Indonesia is currently facing a crisis of digital authority reflected in weak data localization, dependency on foreign platforms, platform asymmetry, and regulatory incapacity. Therefore, a reconstruction of digital governance through the Child Centered Digital Sovereignty model is necessary by strengthening platform regulations, algorithm transparency, age verification systems, child-friendly digital design, and national data sovereignty. This approach is essential to ensure legal protection for children while simultaneously strengthening state sovereignty in the governance of the digital ecosystem.